DISAIN BANTARAN YANG ESTETIS, EKOLOGIS DAN FUNGSIONAL DI SITU PENGARENGAN DEPOK - Qurrotu Aini Besila; Nur Intan Simangunsong; Titiek P Debora; Maria Margaretha Sintorini (JUARA: Jurnal Wahana Abdimas Sejahtera, 2023)
Situ Pengarengan Depok has banks with the potential for the beauty of the landscape that has not been optimally utilized as a city green open space, if it is managed properly and correctly, it can be one of the alternative tourism in Depok. The problems felt by the surrounding community are (1) The occurrence of flooding in the rainy season due to silting, garbage, and plants that spread throughout the banks; (2) The lack of green open space that can be used by the community as  a passive or active recreation area, (3) The lake bank has not been used optimally, and (4) There is no clarity on the authority to manage the lake bank.This Community Service (PkM) aims to (1) socialize the importance of public awareness to participate in conserving the lake and its banks, (2) making a "sustainable lake-banks landscape arrangement" by considering ecological aspects, aesthetic aspects and functional aspects according to community needs. The method used starts from the result of preliminary research, site survey and design process. The design process begins with conducting a physical and non-physical analysis, user analysis, mapping of the needs programs, then followed by generating concept, design schematic, and site plan along Situ Pengarengan. The site plan images are presented to the surrounding community to get feedback through the Forum Group Discussion (FGD), then the result from FGD is used to finalize the product image. The results of the FGD are increasing awareness of community behavior to participate in conserving the lake and its banks, published articles in the PkM journal, copyright for the site plan (Site Plan) and copyright for a simulation video for the design of the Situ Pengarengan riverbank. To conclude, the FGD activity and the site plan design are very functionally, aesthetically and ecologically beneficial for the sustainability of Situ Pengarengan banks.